3D‐isotropic high‐resolution morphological imaging and quantitative T2 mapping as biomarkers for gender related differences after matrix‐associated autologous chondrocyte transplantation (MACT). Issue 10 (11th July 2014) - Pachowsky, Milena L.; Werner, Sven; Marlovits, Stefan; Stelzeneder, David; Renner, Nina; Trattnig, Siegfried; Welsch, Goetz H.
ABSTRACT The aim of this study was to determine in vivo high‐resolution morphological and biochemical gender related differences in cartilage repair tissue (MACT). Forty patients were examined clinically and by MR scans at 3T‐MRI (coronal 3D True‐FISP sequence for morphologic assessment and multi‐echo spin‐echo T2‐mapping for biochemical assessment of healthy cartilage and MACT cartilage). Mean T2 values in repair tissue in the deep zone showed significantly shorter T2 times in females (p = 0.009, female 43.5 ± 9.8 vs. male 48.2 ± 7.7 ms). The superficial zone showed higher T2 values than the deep zone in both the groups (female 48.5 ± 9.8, males 52.6 ± 11.0 ms) without significant difference between female and male patients. Native control cartilage showed no statistically significant differences for T2 between females and males. The subdivisions "structure of the repair tissue" and "subchondral bone" of the MOCART score showed statistically significant differences between females and males (p = 0.026 and p = 0.007) as well as the Lysholm score (p = 0.03). Our investigations revealed differences between female and male patients after MACT of the knee in clinical outcome and advanced morphological and biochemical MRI. The presented imaging biomarkers can depict subtle changes after cartilage regeneration procedures and might help to understand gender related differences after cartilage repair procedures. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:1341–1348, 2014.